Radiological assessment of response and adverse events associated with novel systemic oncological therapies. Issue 4 (April 2021) - Veerasuri, S.; Little, D.; De Paepe, K.N.; Andreou, A.; Bowen, R.; Beresford, M.; Tillett, T.; Gangadhara, S.; Loughborough, W.W.
Abstract : The last decade has seen a paradigm shift in medical oncology treatment with the rise of novel systemic agents, principally molecular targeted therapy and immunotherapy. These new groups of anti-cancer treatment have revolutionised the prognostic landscape for certain patient cohorts with advanced disease, and it is hoped that through ongoing extensive clinical research, significant survival benefits may be demonstrated in the majority of tumour types. However, radiological response assessment of these new agents has become more nuanced for radiologists, as the behaviour of both responding and progressing tumour burden can be more diverse than with conventional chemotherapy. Additionally, radiologists need to be aware of adverse events associated with these treatments as some side effects carry a high morbidity/mortality and may manifest radiologically before they become clinically apparent. This review discusses radiological response assessment and adverse events associated with these novel agents, which have become fundamental aspects of systemic oncological therapy.